Nurses intention to stay in the nursing profession and associated factors in Ethiopia: a systematic review and meta-analysis - Kirubel Eshetu Haile; Yordanos Sisay Asgedom; Atitegeb Alebachew Amsalu; Gizachew Ambaw Kassie; Tsion Zebdiwos Chema; Amanuel Yosef Gebrekidan; Gedion Asnake Azeze (BMC Nursing)
Abstract Introduction The persistent attrition of nurses from the profession is a significant challenge for both healthcare policymakers and administrative bodies within numerous low-income countries. In Ethiopia, various cross-sectional studies have been conducted regarding nurses’ intention to stay in the nursing profession; however, the results have demonstrated inconsistency. Hence, this study aims to pool the level of nurses’ intention to persist in the nursing profession. Methods In our systematic review and meta-analysis, targeted findings were searched from a variety of electronic databases; including Pub Med, Google Scholar, African Journal Online, the Cochran Library, and Science Direct. To determine the pooled prevalence and associated factors of intent to stay in nursing profession among nurse in Ethiopia, all the necessary data was extracted by using a standardized data extraction format. We analyzed the data by using Stata 17 statistical software. Heterogeneity between the primary studies was assessed by I-square tests. A random-effect model was applied to estimate the pooled intention of nurses to continue within the nursing profession. Result We included a total of 12 full-text studies in our analysis. The findings of this meta-analysis revealed that the pooled prevalence of nurses' intention to stay in nursing profession among Ethiopian nurses was 45.57% (95% CI; 38.43, 52.72). The subgroup analysis data revealed that the highest pooled prevalence of intention to stay was reported in the Tigray region which is 56.1% (95% CI 52.24, 59.96). In contrast the lowest prevalence was documented in Addis Ababa city administration which was 19.4% (95% CI 15.56, 23.24). Factors such as job satisfaction (OR = 2.69, 95% CI = 1.11 – 6.53), professional development (OR = 2.49, 95%CI = 1.27- 4.9), level of education (OR = 2.7, 95% CI = 1.92–3.8), payment and benefit (OR = 1.9, 95%CI = 1.15- 3.19) all were the significant determinants of nurses’ intention to continue in the nursing profession. Conclusion The results of our investigation suggested that the degree of intention to continue in the nursing profession among Ethiopian nurses was inadequate. The nurses' intention to depart from the nursing profession is an alarming. Therefore, it’s imperative for healthcare policymakers and stakeholders to prioritize on retention strategies encompassing job satisfaction, recognition, incentives, career opportunities, professional support, and autonomy were necessary.